Zhuang handicraft in the Baise area: The gendered cultural significance of Mo-Mie - Xiaoqin Zhou; Hongshen Zhang; Musnin Misdih (Akademi Seni dan Teknologi Kreatif, UMS, 2021)
This research is of interest at local, Chinese national, and global levels. Locally, I examine the cultural production of the Zhuang people around Baise in the Guangxi Zhuang Autonomous Region, the Zhuang being one of the 56 official nationalities in China. Globally, there is increasing interest in China and its make-up, including the specific national cultural components. I attempt to contribute to clarity in attaching aesthetic and social value to cultural production that is often carried out by women and largely categorised as ‘craft’, rather than ‘art’. I adopt an empirical approach by engaging with the producers of such work and examine their relationship to the processes of its consumption. I found that the traditional family handcraft of Mo-Mie had been largely forgotten until coming back into focus in 2009 due to government efforts to explore China's national cultures. This short piece of research cannot ‘solve’ the problems that face the history of art. My attempt, in a limited way, is continue the process of examination and appreciation of unique forms of cultural production that exist, in order that we might begin to develop wider conclusions about the place of such creativity in appreciation of human heritage.